Kinematic stability of a 2-DOF deployable translational parallel manipulator. (June 2021) - Yang, Yi; Tang, Lei; Zheng, Huayong; Zhou, Yang; Peng, Yan; Lyu, Shengnan
Highlights: Propose a method for examining the stability of parallel mechanisms. Define and analyze the virtual deformation energy of a 2-dof DTPM. Clarify the effect of number and location of middle links on stability of the DTPM. Propose an effective method for improving the stability of the mechanism. Fabricate a prototype and test the feasibility and stability of the manipulator. Abstract: In this paper, kinematic stability of a 2-degree-of-freedom (dof) deployable translational parallel manipulator (DTPM) with dual scissor-like mechanisms (D-SLiMs) is investigated; method for improving the stability of the manipulator is proposed. First, the virtual deformation energy of links is defined. Multiple workspace components of the DTPM are obtained by solving the minimization problem of deformation energy. To evaluate the local stability of the mechanism, the Hessian matrix of the deformation energy is studied for obtaining the instantaneous performance; then, the passing energy of virtual deformation within a finite range is analyzed. Based on that, the relative range of 2 categories of the idle motions is explored in the whole workspace. Next, the influence of the number and the locations of the middle links on the stability and stiffness of the DTPM is evaluated. Accordingly, a method for improving kinematic stability is proposed. A prototype is fabricated; its stability during motion is validated in the pick-and-place experiments. Since it is collapsible for easy storage, and can be deployed for a variety of operations, the prototype is applied on an Unmanned Aerial Vehicle (UAV) and taken into the test flight.